(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article examines the historical and theoretical foundations of educational services through the prism of the ideas of ancient and medieval Eastern thinkers. Particular attention is paid to the views of Al-Farabi, Ibn Sina (Avicenna), Yusuf Khos Hajib, Alisher Navoi, Mirzo Ulugbek and other representatives of the scientific and philosophical heritage of Central Asia. The study reveals the role of education in personality development, moral upbringing, human capital formation and social progress. It is argued that education was regarded not only as a means of knowledge transmission but also as a foundation for just governance, public welfare and economic development. The article concludes that the intellectual heritage of Eastern thinkers remains highly relevant for understanding educational services as a strategic resource for the socio-economic development of the Republic of Uzbekistan.